Gradient electromagnetic forming (GEMF): A new forming approach for variable-diameter tubes by use of sectional coil. (December 2018) - Li, Jianjun; Qiu, Wei; Huang, Liang; Su, Hongliang; Tao, Huan; Li, Peiyue
Abstract: A new gradient electromagnetic forming (GEMF) approach that utilizes the gradient electromagnetic force generated by use of a sectional coil is proposed to meet force-field requirements concerning deformation of specially shaped variable-diameter tubes. To demonstrate the development of this approach, a variable-diameter tube made of copper-nickel alloy was formed via GEMF, as an example. An efficient geometric design for the sectional coil was established, and effects of the gradient electromagnetic force field on metal flow have been discussed along with investigation of the effects of key process parameters on tube forming. The deformation mechanism of GEMF has also been explained. Feasibility of the GEMF approach has been validated based on the accurate deformations of variable-diameter tubes made of copper-nickel alloy and characterized by a maximum die-fitting gap of less than 0.4 mm. Moreover, optimal combination of the coil proportion coefficient (85%) and discharge voltage (18 kV) have been obtained to ensure high forming accuracy. It was observed that the gradient electromagnetic force field prevented occurrence of stress concentrations by effectively improving stress distributions. Consequently, the forming accuracy and quality of variable-diameter tubes was significantly improved using the GEMF approach. Graphical abstract: Highlights: GEMF utilizing gradient electromagnetic force field produced by sectional coils is proposed. Effects of key process parameters on the variable-diameter tube deformation by GEMF is analyzed and discussed. GEMF improves forming accuracy and quality by releasing uneven stress distributions.